2014
DOI: 10.1007/s10997-014-9304-y
|View full text |Cite
|
Sign up to set email alerts
|

Directors’ human capital, firm strategy, and firm performance

Abstract: Ideally, corporations are directed by boards whose directors provide valuable human capital that match the firms' strategy. We investigate how directors' human capital (international experience, industrial know-how, CEO experience, and financial know-how) affects firm performance including the firm's strategy (diversification and internationalization) and how human capital is related to acquisition strategies (non-diversifying and international acquisitions). Our sample consists of 560 firm-year observations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 145 publications
2
27
0
1
Order By: Relevance
“…In what concerns the values bounding the conceptual framework-in line with Webster and Watson [57]-it is our belief that the multicriteria approach of the triad intellectual capital-SMEs internationalization-sustainable competitive advantage would become a good starting point for other scholars to make sense of the accumulated knowledge in the field via the multidisciplinary perspectives, beginning with the topic's central ideas towards the related key findings and relationships among variables. Hereby, the identified research areas which mainstream the relationship between intellectual capital and SMEs internationalization through the lens of sustainable competitive advantage fall under the following main directions and/or conceptual frameworks: (a) strategic alliances, e.g., [18,36,63,64], (b) social and business networks, e.g., [8,50,51,65,66], (c) business skills, e.g., [36,46,55,67], (d) pursue or achievement of sustainable competitive advantage, e.g., [19,36,68,69], (e) SMEs performance, e.g., [13,29,50,70], (f) family-owned business, e.g., [24,[71][72][73][74], (g) prior international experience, e.g., [55,[75][76][77], (h) knowledge transfer, e.g., [12,78,79], (i) institutional/governmental programs, e.g., [19,47,80,81], (j) business/organizational innovation, e.g.,…”
Section: Methodsmentioning
confidence: 99%
“…In what concerns the values bounding the conceptual framework-in line with Webster and Watson [57]-it is our belief that the multicriteria approach of the triad intellectual capital-SMEs internationalization-sustainable competitive advantage would become a good starting point for other scholars to make sense of the accumulated knowledge in the field via the multidisciplinary perspectives, beginning with the topic's central ideas towards the related key findings and relationships among variables. Hereby, the identified research areas which mainstream the relationship between intellectual capital and SMEs internationalization through the lens of sustainable competitive advantage fall under the following main directions and/or conceptual frameworks: (a) strategic alliances, e.g., [18,36,63,64], (b) social and business networks, e.g., [8,50,51,65,66], (c) business skills, e.g., [36,46,55,67], (d) pursue or achievement of sustainable competitive advantage, e.g., [19,36,68,69], (e) SMEs performance, e.g., [13,29,50,70], (f) family-owned business, e.g., [24,[71][72][73][74], (g) prior international experience, e.g., [55,[75][76][77], (h) knowledge transfer, e.g., [12,78,79], (i) institutional/governmental programs, e.g., [19,47,80,81], (j) business/organizational innovation, e.g.,…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the majority of previous studies on board human capital have focussed only on board independence, and found mixed results between board characteristics and firm outcomes (K. Campbell and Vera, 2010;Dionne and Triki, 2004;Hill, 2013, Marsden andPrevost, 2005;Volonté and Gantenbein, 2016). The inconclusive results may stem from the fact that previous studies have only considered one attribute of the board of directors and omitted other important variables.…”
Section: Motivationmentioning
confidence: 98%
“…The inconclusive results may stem from the fact that previous studies have only considered one attribute of the board of directors and omitted other important variables. Most importantly, researchers have argued that board independence is not an important board human capital characteristic, as it does not provide a good scope of the board's role (Volonté and Gantenbein, 2016). Therefore, there is a growing demand to examine more relevant human capital characteristics, such as specific skills and experience, as suggested by resource dependency theory (Fama and Jensen, 1983;Johnson, Schnatterly and Hill, 2013;Volonté and Gantenbein, 2016).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste sentido, pesquisas têm sido realizadas com o propósito de compreender o processo de internacionalização das empresas (AMAL et al, 2010;MORAES et al, 2012;PLATCHEK;FLO-RIANI, 2013;PETRY et al, 2014 (CHILD, 1972;VAHLNE, 1977;MINTZBERG, 1978;REID, 1983;MINT-ZBERG;WATERS, 1985;PETTIGREW, 1987;OLIVEIRA et al, 2009;STRANGE et (CHANDLER, 1962;PENROSE, 1979;PORTER, 1986;BAR-TLETT;GHOSHAL, 1987;MELIN, 1992;HOSKISSON el al, 1993;SULLIVAN, 1994;HOSKISSON et al, 2009;KOVACS, 2009;KWEE;VAN DEN BOSCH;VOLBERDA, 2011;YORKS;NICOLAIDES, 2012;SZCZEPAŃSKI;ŚWIATOWIEC-SZCZEPAŃSKA, 2012;BOD-NARUK;MASSA;SIMONOV, 2013;LIEN;LI, 2013;ZILLI;VIEIRA;HEINZEN, 2015;VO-LONTÉ;GANTENBEIN, 2016); 4. Contexto interno: recursos tangíveis e intangí-veis, competência desenvolvidas, evidencia-se a influência no processo de internacionalização a partir dos recursos tangíveis e intangíveis, das competências desenvolvidas e inerentes às empresas …”
Section: Pressupostos Teóricosunclassified